2007
DOI: 10.1021/bi701112z
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Molecular Mechanism of Metal-Induced Aβ (1−40) Amyloidogenesis

Abstract: Transition-metal ions (Cu2+ and Zn2+) play critical roles in the Abeta plaque formation. However, precise roles of the metal ions in the Abeta amyloidogenesis have been controversial. In this study, the molecular mechanism of the metal-induced Abeta oligomerization was investigated with extensive metal ion titration NMR experiments. Upon additions of the metal ions, the N-terminal region (1-16) of the Abeta (1-40) peptide was selectively perturbed. In particular, polar residues 4-8 and 13-15 were more strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 80 publications
4
75
0
Order By: Relevance
“…Uniquely, equimolar conditions exhibit decreased initial metal-induced A␤ aggregation and a slow constant disappearance rate of both A␤ and Cu(II). An explanation could be that several conformations of the soluble Cu-A␤ complex exist (42,58), and that the conformational equilibrium of this complex is affected by the metal:peptide ratio (16,23,39). EPR (62)(63)(64) and stopped-flow fluorescence experiments (27) with A␤ and Cu(II) confirm the co-existence of at least two different A␤-Cu conformations at neutral pH.…”
Section: Aβ Monomermentioning
confidence: 93%
See 1 more Smart Citation
“…Uniquely, equimolar conditions exhibit decreased initial metal-induced A␤ aggregation and a slow constant disappearance rate of both A␤ and Cu(II). An explanation could be that several conformations of the soluble Cu-A␤ complex exist (42,58), and that the conformational equilibrium of this complex is affected by the metal:peptide ratio (16,23,39). EPR (62)(63)(64) and stopped-flow fluorescence experiments (27) with A␤ and Cu(II) confirm the co-existence of at least two different A␤-Cu conformations at neutral pH.…”
Section: Aβ Monomermentioning
confidence: 93%
“…In all events elucidating the underlying molecular mechanisms of the A␤-Cu, interactions are vital for understanding the role of Cu(II) in the pathology of AD, and hence in developing new therapeutic strategies for the treatment of AD (7,22). Despite extensive studies, however, these mechanisms remain largely unsettled and conflicting effects have been reported; in some studies Cu(II) appears to be involved in amyloid oligomerization (4,23,24), other studies report that Cu(II) does enhance aggregation but only along non-amyloidogenic pathways (17,25), or even that Cu(II) inhibits the aggregation of A␤ (26). We recently showed that Cu(II) could induce both oligomerization and non-oligomerization pathways of A␤ on the millisecond-second time scale (27).…”
mentioning
confidence: 99%
“…Zinc has a crucial role in Ab aggregation, which is the most well-established contribution that zinc may have in AD pathogenesis. Aggregation of Ab peptides into protease-resistant deposits can be rapidly induced in the presence of zinc ions under physiological conditions in vitro (34,35). Zn binds to Ab in a monomeric and stoichiometric Zn-Ab complex, which is transiently stable prior to aggregation; the structure of the aggregates was described to be more amorphous, i.e., to contain less fibril (36).…”
Section: Zincmentioning
confidence: 99%
“…Studies suggested that H6, H13, and H14 at the N-terminal domain of Aβ coordinate with Zn 2þ (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Solution NMR of Zn 2þ -Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] showed that Zn 2þ is bound to these three histidines and E11 (18). A recent NMR study of Zn 2þ -Aβ proposed that Zn 2þ binds to H6, E11, H14, and D1 of rat Aβ 1-28 and to H6, E11, H13, H14, and D1 of human Aβ 1-28 (22).…”
mentioning
confidence: 99%